STRATEGI GURU DALAM PENGELOLAAN KELAS UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS V PADA MATA PELAJARAN AQIDAH AKHLAK DI MIS TARBIYAH TEBAS - Nurmala Nurmala (Tarbiya Islamica, 2014)
This study aims to obtain information about: 1) The strategy of the teacher to use the means in class management to increase the learning motivation of class V students in the subject of aqidah akhlak in MIS Tarbiyah Tebas in the 2019-2020 school year; 2) The steps of the teacher in class management to increase the learning motivation of grade V students in the subject of aqidah akhlak at MIS Tarbiyah Tebas in the 2019-2020 academic year. This research uses a qualitative approach and descriptive research type. The subjects of this study were the MIS Tarbiyah Tebas moral aqidah teachers and fifth grade students at MIS Tarbiyah Tebas. The technique of collecting data using interview, observation and documentation methods. The data analysis technique used is qualitative data analysis. In this study, researchers used two data validity checking techniques, namely: 1) Triangulation Technique, 2) Member Check Technique. The results of the study can be concluded that: 1) The strategy of the teacher using the facilities in class management to increase the learning motivation of class V students in the subject of aqidah akhlak in MIS Tarbiyah Tebas in the 2019-2020 academic year, namely: a) the management of classrooms, classrooms is adequate; b) the seating arrangement is varied; c) learning methods: using appropriate and varied methods, for example the lecture method, the question and answer method and the training method; d) use of media: using appropriate media and in accordance with the material presented, utilizing the environment, teacher's books, student worksheets (LKS), image media; e) a good pattern of interaction so as to create a harmonious relationship between teachers and students. 2) The steps of the teacher in class management to increase the learning motivation of grade V students in the subject of aqidah akhlak at MIS Tarbiyah Tebas in the 2019-2020 school year, while the steps are taken, namely: a) planning which consists of compiling learning tools (programs annual, semester program, educational calendar, syllabus and lesson plans). b) implementation of classroom management to increase student learning motivation: creating a conducive classroom climate/ atmosphere, opening lessons, evaluating learning.